Ginger, Pepper and Curry Leaf Powder as Feed Additives in Broiler Diet - Moorthy, M.; Ravi, S.; Ravikuma, M.; Viswanathan, K.; Edwin, S.C. (International Journal of Poultry Science, 2009)
Two hundred and ten commercial, straight run day-old Vencobb broiler chicks belonging to single hatch were purchased from local hatchery, wing banded, weighed and randomly allotted into seven treatment groups with three replicates of ten chicks each. The chicks were reared in broiler cages in a gable roofed, open sided house. All the chicks were provided with uniform floor, feeder and waterer space and were reared under standard management conditions throughout the experimental period of six weeks. The treatments were T1-Control; T2-0.2% Ginger powder; T3-0.2% Pepper powder; T4-0.2% Curry leaf powder; T5-0.2% Ginger + 0.2% pepper; T6-0.2% Ginger + 0.2% Curry leaf powder and T7-0.2% Pepper + 0.2% Curry leaf powder. The mean body weight (g/bird) of broilers at 6 weeks of age fed with different inclusion levels of dried ginger, pepper and curry leaf powder differ significantly (p